2018
DOI: 10.1002/ceat.201700315
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Methane Decomposition to Hydrogen over a Surface‐Protected Core‐Shell Ni@SiO2 Catalyst

Abstract: Methane decomposition is a promising method to obtain CO x -free hydrogen. The main difficulty of this process is that the produced carbon would deposit on the active phase of the catalyst, leading to catalyst deactivation. In this study, a coreshell-structured composite catalyst comprising highly active Ni nanoparticles (NP) as core and mesoporous silica as shell is introduced. The silica shells were synthesized by using cetyltrimethylammonium bromide as template and tetraethyl orthosilicate as precursor. Ni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…By varying the GHSV from 5000 to 24 000 mL g −1 hour −1 , a significant reduction in methane conversion is not observed. The porous silica support used in their study is concluded to effectively adsorb methane, permitting a sufficient contact time for the decomposition of methane even under varied GHSV conditions 113 . Moreover, at a higher GHSV, the deactivation rate increases 114,142 .…”
Section: Ni‐based Catalystmentioning
confidence: 95%
See 2 more Smart Citations
“…By varying the GHSV from 5000 to 24 000 mL g −1 hour −1 , a significant reduction in methane conversion is not observed. The porous silica support used in their study is concluded to effectively adsorb methane, permitting a sufficient contact time for the decomposition of methane even under varied GHSV conditions 113 . Moreover, at a higher GHSV, the deactivation rate increases 114,142 .…”
Section: Ni‐based Catalystmentioning
confidence: 95%
“…As oxide supports, metal oxides such as Al 2 O 3, 21,80,97,107 TiO 2, 108,109 SiO 2, 79,110‐114 MgO, 101,115 CeO 2, 100,116 ZrO 2, 23,94 and zeolite 22,104 are frequently used for a Ni‐based catalyst. In practice, active metal particles must be dispersed onto the oxide support surface.…”
Section: Ni‐based Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of active metal (primarily Fe, Ni, Co, and combinations thereof), catalyst support (e.g., SiO 2 , , Al 2 O 3 , , MgO, ZrO 2 , TiO 2, CeO 2 , , La 2 O 3 ), promoters (e.g., noble metals, group VIB metals, and base-metal alloys), and preparation methods (e.g., impregnation, , solid-state fusion, evaporation-induced self-assembly, and sol–gel) on reaction rates, catalyst stability and product morphology have all been studied extensively in recent years. In contrast, few studies , have investigated low-temperature (<500 °C) CMD despite the potentially significant reduction in operating costs and heating-related carbon emissions from milder operating conditions. Importantly, the unfavorable effect of lower temperatures on the equilibrium conversion can be mitigated by continuously separating H 2 using H 2 -permeable membranes. As carbon diffusion and precipitation rates with different temperature sensitivities must be carefully balanced for optimal catalyst activity and stability, catalysts that are optimized for higher-temperature CMD may not perform equally well at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The Ni/SiO 2 catalyst showed a good conversion of methane but less yield of hydrocarbons. Methane is decomposed to H 2 and C on the Ni/SiO 2 catalyst, as previously reported. , When earlier d-block metals than Ni (Mn, Fe, Co) were added as a second element to Ni on SiO 2 , the selectivity to hydrocarbons and yields were as low as those observed for Ni/SiO 2 catalyst. However, methane conversions of these d-block metals were higher than that of Ni/SiO 2 .…”
mentioning
confidence: 99%